Optimal operation of cascaded hydropower plants in hydro-solar complementary systems considering the risk of unit vibration zone crossing - Haoting, Qin; Tianzhi, Li; Jianhua, Li; Yunxia, Wu; Hongtao, Song (Frontiers in Energy Research, 2023)
With the strategic realignment of the national energy structure of China, clean energy has become the main development direction of the future. Developing cascaded hydropower plants in hydro-solar complementary systems is an important way to optimize the energy structure and break through the constraints of resources and environment. This paper focus on the risk that solar energy disturbances can easily induce low-frequency oscillations, resulting in large-scale load transfer between hydropower units in a short period of time and hydropower units frequently crossing their vibration zones. Vibration zone crossing can further cause wear of mechanical components of hydropower units. Considering the requirement of avoiding vibration zone crossing, the concept of vibration zone crossing risk coefficient is introduced and a cascaded hydropower plant optimal operation model considering the risk of vibration zone crossing is proposed. Moreover, a biogeography based optimization and dynamic programming (BBO-DP) combined two-layer algorithm with improved migration model and migration operator is pro-posed to solve the model. Numerical simulation results based on data of an actual hydropower plant validate the proposed model and algorithm.